THE ROLE AND SCIENTIFIC LEGACY OF MIRZO ULUGBEK IN THE DYNASTY OF AMIR TIMUR - Voroshilova Feruza Alisher qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. Mirzo Ulugʻbek was one of the most prominent representatives of the Timurid dynasty and a famous astronomer of the medieval period. This article analyzes his political role within the dynasty founded by Amir Temur and highlights his scientific achievements. Particular attention is given to the establishment of the scientific school in Samarkand and the construction of the Ulugʻbek rasadxonasi. The importance of his astronomical work “Zij-i Jadid-i Guragani” for the development of world astronomy is also discussed.